2012
DOI: 10.1007/s11802-012-1799-8
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of microbial populations and their relationship with environmental variables in the North Yellow Sea, China

Abstract: In order to understand the large-scale spatial distribution characteristics of picoplankton, nanophytoplankton and virioplankton and their relationship with environmental variables in coastal and offshore waters, flow cytometry (FCM) was used to analyze microbial abundance of samples collected in summer from four depths at 36 stations in the North Yellow Sea (NYS). The data revealed spatial heterogeneity in microbial populations in the offshore and near-shore waters of the NYS during the summer. For the surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 53 publications
0
5
1
1
Order By: Relevance
“…As still little is known about viral community dynamics in petroleum reservoirs, more efforts are needed to investigate the viral distribution, abundance, and diversity in the underground ecosystem. Compared with the viral abundance in other environments, for example, aquatic environment, the abundance of viruses in the petroleum reservoir was in a different order of magnitude as those previously reported in aquatic environments, including marine [ 42 , 43 , 44 ], stormwater retention ponds [ 45 ], and tropical estuaries [ 46 ]. Interestingly, the virus abundance of production wells in the microbial flooding block was slightly higher than that in the water flooding block.…”
Section: Discussionmentioning
confidence: 75%
“…As still little is known about viral community dynamics in petroleum reservoirs, more efforts are needed to investigate the viral distribution, abundance, and diversity in the underground ecosystem. Compared with the viral abundance in other environments, for example, aquatic environment, the abundance of viruses in the petroleum reservoir was in a different order of magnitude as those previously reported in aquatic environments, including marine [ 42 , 43 , 44 ], stormwater retention ponds [ 45 ], and tropical estuaries [ 46 ]. Interestingly, the virus abundance of production wells in the microbial flooding block was slightly higher than that in the water flooding block.…”
Section: Discussionmentioning
confidence: 75%
“…Prochlorococcus was not detected in all samples. Previous studies showed that although Prochlorococcus was detected in the offshore waters of East China Sea and South China Sea, they were not detected in the Yellow Sea and Bohai Sea ( Jiao and Yang, 2002 ; Jiao et al, 2002 , 2005 ; Bai et al, 2012 ; Guo et al, 2014 ).…”
Section: Resultsmentioning
confidence: 95%
“…pH can directly affect the growth of microorganisms and affect the community structure and diversity of microorganisms by changing the physical and chemical properties of water (Yannarell et al 2005, Langenheder et al 2006). Chl-a was a good indicator of the stock of phytoplankton (Bai et al 2009), and studies found that planktonic bacteria were closely related to the community structure of phytoplankton (Kirchman et al 1991, Teeling et al 2012. Bacteria not only absorb the organic matter produced by phytoplankton but also provide organic nutrients and growth factors for phytoplankton.…”
Section: Discussionmentioning
confidence: 99%